Antecedents of export performance : empirical evidence from Malaysian construction professional consultants / Datuk Ir Haji Abdul Latif Mohd Som - Mohd Som, Abdul Latif (Institute of Graduate Studies, UiTM, 2014)
The effects of globalization have resulted in many firms exploring beyond their national boundaries in search of a better business performance. Resulting therefrom, increasing efforts have been made by researchers in the recent past in order to determine the antecedents of export venture performance of firms in addition to defining the appropriate dimensions of export performance. The objectives of this study are: (i) to explore the possible dimensions of export performance including its relationship between one dimension and another, (ii) to identify the main antecedent variable to export performance, (iii) to analyze the relationships between one antecedent variable and another, and (iv) to analyze the moderating effects of the 4 moderators on five critical links. Data were collected from 55 participating firms which were drawn from the Malaysian Construction Professional Consultants specifically those which are construction.